2022
DOI: 10.1515/znc-2021-0193
|View full text |Cite
|
Sign up to set email alerts
|

Scopoletin: a review of its source, biosynthesis, methods of extraction, and pharmacological activities

Abstract: Scopoletin, also known as 6-methoxy-7 hydroxycoumarin, is one of the naturally occurring coumarin commonly found in many edible plants and plays an important role in human health. Despite the various potential pharmacological properties, the biosynthesis process, method of extraction, and mechanism of action on this compound have not been documented well. In this current review, the biosynthesis pathway, distribution of scopoletin in the plant kingdom, and extraction techniques are elaborated. The in vitro, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 126 publications
3
17
0
1
Order By: Relevance
“…Scopoletin is a coumarin phytoalexin essential for the plant defense mechanism. The resistance to microbial attack is correlated with the biosynthesis and accumulation of scopoletin; hence, it is a potent antibacterial and antifungal agent . A previous study reported that scopoletin isolated from Pelargonium sidoides roots exhibited antitubercular activity toward Mycobacterium smegmatis with an MIC value of 7.81 μg/mL .…”
Section: Resultsmentioning
confidence: 99%
“…Scopoletin is a coumarin phytoalexin essential for the plant defense mechanism. The resistance to microbial attack is correlated with the biosynthesis and accumulation of scopoletin; hence, it is a potent antibacterial and antifungal agent . A previous study reported that scopoletin isolated from Pelargonium sidoides roots exhibited antitubercular activity toward Mycobacterium smegmatis with an MIC value of 7.81 μg/mL .…”
Section: Resultsmentioning
confidence: 99%
“…Scopoletin, also known as 6-methoxy-7 hydroxycoumarin, is an active component of noni fruit that has antioxidant activity and medicinal properties such as blood dilution. It is one of the natural coumarin compounds found in several types of plants usually consumed for health [27]. The coumarin compound has been reported to start to degrade after 60 minutes of heating at 200℃ or higher temperature and remain stable at 100-150℃ or lower temperature [28].…”
Section: Post-drying Qualitymentioning
confidence: 99%
“…As regards bactericide and fungicide activities of other phytochemicals identified in the H. stoechas inflorescence extract, there are references on the activities of scopoletin [38,39], maltol [40], and quinic acid [41,42]. Scopoletin inhibits Gram-positive bacteria, such as Enterococcus faecium and S. aureus (MIC = 128 µg mL −1 ), as well as Gram-negative bacteria, such as Stenotrophomonas maltophila (MIC = 256 µg•mL −1 ), and quinic acid derivatives were effective against fungi [43] and S. aureus [44].…”
Section: On the Phytochemical Profilementioning
confidence: 99%